2019
DOI: 10.3390/cells8111343
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the Tks4 Scaffold Protein Induces Epithelial-Mesenchymal Transition-Like Changes in Human Colon Cancer Cells

Abstract: Epithelial to mesenchymal transition (EMT) is a multipurpose process involved in wound healing, development, and certain pathological processes, such as metastasis formation. The Tks4 scaffold protein has been implicated in cancer progression; however, its role in oncogenesis is not well defined. In this study, the function of Tks4 was investigated in HCT116 colon cancer cells by knocking the protein out using the CRISPR/Cas9 system. Surprisingly, the absence of Tks4 induced significant changes in cell morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 63 publications
4
26
0
Order By: Relevance
“…A novel function of TKS4 in EMT-like processes has been recently discovered by Szeder and colleagues [153]. During EMT, epithelial cells lose epithelial features and functions.…”
Section: Absence Of Tks4 Induces Epithelial-mesenchymal Transition (Emt) and Promotes Invasive Behaviormentioning
confidence: 91%
See 2 more Smart Citations
“…A novel function of TKS4 in EMT-like processes has been recently discovered by Szeder and colleagues [153]. During EMT, epithelial cells lose epithelial features and functions.…”
Section: Absence Of Tks4 Induces Epithelial-mesenchymal Transition (Emt) and Promotes Invasive Behaviormentioning
confidence: 91%
“…Szeder et al hypothesized that a temporary loss of TKS4 could negatively affect podosome-related cell migration (as described earlier), while the prolonged effect of the absence of the molecule could be increased invasiveness by activating an EMT-like program. They also concluded that the molecule might act differently in cells of epithelial origin (like HCT116) than in those of mesenchymal origin [153]. Despite these interesting findings on the role of TKS4 in EMT processes, more studies are needed to confirm the results of Szeder et al and to elucidate the exact mechanisms behind this phenomenon.…”
Section: Absence Of Tks4 Induces Epithelial-mesenchymal Transition (Emt) and Promotes Invasive Behaviormentioning
confidence: 97%
See 1 more Smart Citation
“…The expression levels of N-cadherin and E-cadherin are important biomarkers of EMT progress ( 11 ). Previous studies have reported that EMT participates during colon cancer carcinogenesis and development ( 12 ); therefore, identifying novel therapeutic targets to prevent EMT may be valuable for CRC.…”
Section: Introductionmentioning
confidence: 99%
“…In FTHS-affected individuals, the development of several tissues is disturbed [ 23 , 24 ], showing that Tks4 has an effect on bone, fat, and mesenchymal stem cells [ 25 , 26 ]. Moreover, Tks4 has an instructive role in an epithelial mesenchymal (EMT)-like transition in cancer cells [ 27 ]. Although multiple functions of Tks4 have been described, its exact role and position in signaling pathways and the molecular mechanisms underlying its regulation remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%